Association of Physical Performance and Pain With Fear of Falling Among Community—Dwelling Japanese Women Aged 65 Years and Older. Issue 35 (September 2015) - Tomita, Yoshihito; Arima, Kazuhiko; Kanagae, Mitsuo; Okabe, Takuhiro; Mizukami, Satoshi; Nishimura, Takayuki; Abe, Yasuyo; Goto, Hisashi; Horiguchi, Itsuko; Aoyagi, Kiyoshi
Abstract : Abstract: Our aim was to explore the association of physical performance and pain with fear of falling among community-dwelling Japanese women. The subjects were 278 women aged 65 years and over. We collected information on fear of falling, painful joints, comorbidities, falls in the previous year, and cataracts. Walking time (distance of 6 m), chair stand time (5 times), grip strength, the timed up and go test (TUG), and functional reach were measured. The prevalence of fear of falling was 36.3%, and it increased with age, but it was not significant ( P  = 0.081). Multivariate logistic regression analysis showed that poor physical performance (longer walking time, longer chair stand time, weaker grip strength, and longer TUG) and pain (low back, and upper and lower extremity pain) were significantly associated with fear of falling after adjusting for age, body mass index, comorbidities, falls in the previous year, and cataracts. Maintaining physical functioning and managing pain may be important for elderly women with fear of falling.